2010
DOI: 10.1016/j.jpain.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Opioids, Chronic Pain, and Addiction in Primary Care

Abstract: Research has largely ignored the systematic examination of physicians’ attitudes towards providing care for patients with chronic non-cancer pain. The objective of this study was to identify barriers and facilitators to opioid treatment of chronic non-cancer pain patients by office-based medical providers. We used a qualitative study design using individual and group interviews. Participants were twenty-three office-based physicians in New England. Interviews were audiotaped, transcribed, and systematically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 40 publications
6
111
0
4
Order By: Relevance
“…Previous surveys have shown that PCPs have concerns about the prescribing of opioids and are fearful of contributing to addiction. In addition, PCPs note the deficiency in primary care education and training in pain management, and question their capacity to provide optimal pain care [15][16][17][18][19]. Limitations of this research include the fact that some of these studies targeted subsets of the broader population of primary care patients with CNCP such as patients having high rates of opioid utilization or addiction, or included providers other than PCPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous surveys have shown that PCPs have concerns about the prescribing of opioids and are fearful of contributing to addiction. In addition, PCPs note the deficiency in primary care education and training in pain management, and question their capacity to provide optimal pain care [15][16][17][18][19]. Limitations of this research include the fact that some of these studies targeted subsets of the broader population of primary care patients with CNCP such as patients having high rates of opioid utilization or addiction, or included providers other than PCPs.…”
Section: Resultsmentioning
confidence: 99%
“…More information is particularly needed about the experiences and attitudes of PCPs serving the population of veterans. There are even fewer studies using qualitative analysis [17,19,20]. Qualitative research offers a method of inquiry that values the identification of the human experience related to a phenomenon of interest and may provide a more complete understanding of PCPs' attitudes and experiences about pain management.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, given office-based provider concerns that patients may be inappropriately using prescription opioid analgesics to manage psychiatric symptomatology, further research assessing the medical and psychiatric co-morbidity of opioid dependent patients with pain entering BNT may be warranted. 10 Several potential limitations are worth considering. Participants were seeking BNT as part of a research study; thus, our findings may or may not generalize to non-research-based BNT programs.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Providers report difficulty and frustration treating patients with co-occurring opioid dependence and chronic pain, defined here as non-cancer physical pain lasting at least three months. [9][10][11] Research to date on chronic pain and its associated morbidity and treatment implications among opioid dependent patients has focused on patients: a) in detoxification programs, 4,7,12,13 b) seeking methadone maintenance treatment (MMT), 14,15 or c) already enrolled in MMT. 1-3, 6, 8, 16 Office-based buprenorphine-naloxone treatment (BNT) is a relatively new treatment modality for opioid dependence in the U.S. and internationally, which in comparison to MMT has attracted a new and different population of opioid dependent patients into opioid agonist treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although specialized multidisciplinary pain treatment is necessary and effective, particularly for more complex patients [8][9], access to these services is limited and is often not needed [7,10]. Thus, while most patients with chronic pain are treated by a primary care provider (PCP), most PCPs face organizational and administrative barriers to providing effective care [11], receive limited training in pain management [12][13], express low confidence in their ability to care for such patients [14][15][16][17], and hold reservations regarding treatment of chronic pain. Studies suggest that there is wide variability in PCPs' adherence to guidelines for pain management [18][19][20], and documentation of comprehensive pain care plans and specific treatment provided is poor [21][22].…”
Section: Introductionmentioning
confidence: 99%